Nucleoside triphosphate-dependent restriction enzymes - Dryden, D. T. F. (Oxford University Press, 2001)
The known nucleoside triphosphate-dependent restriction enzymes are hetero-oligomeric proteins that behave as molecular machines in response to their target sequences. They translocate DNA in a process dependent on the hydrolysis of a nucleoside triphosphate. For the ATP-dependent type I and type III restriction and modification systems, the collision of translocating complexes triggers hydrolysis of phosphodiester bonds in unmodified DNA to generate double-strand breaks. Type I endonucleases break the DNA at unspecified sequences remote from the target sequence, type III endonucleases at a fixed position close to the target sequence. Type I and type III restriction and modification (R-M) systems are notable for effective post-translational control of their endonuclease activity. For some type I enzymes, this control is mediated by proteolytic degradation of that subunit of the complex which is essential for DNA translocation and breakage. This control, lacking in the well-studied type II R-M systems, provides extraordinarily effective protection of resident DNA should it acquire unmodified target sequences. The only well-documented GTP-dependent restriction enzyme, McrBC, requires methylated target sequences for the initiation of phosphodiester bond cleavage.